Components of the Endocannabinoid System and Effects of Cannabinoids Against Bone Diseases: A Mini-Review - Xin, Yuqi; Tang, Anqun; Pan, Shuting; Zhang, Jie (Frontiers in Pharmacology, 2022)
Background: The endocannabinoid system (ECS) is involved in multiple physiological processes, including appetite regulation, pain perception, motor function development, and immune response regulation. Cannabinoids have been approved for the clinical treatment of nausea and vomiting caused by cytostatic therapy or cancer chemotherapy, loss of appetite in HIV/AIDS-associated cachexia, refractory spasms induced by multiple sclerosis, chronic pain, and urinary incontinence. Methods: Check out the research on ECS and bone diseases in the past 20 years. Results: Many studies have demonstrated that endocannabinoids (eCBs) and cannabinoid receptors (CBRs) are expressed in bone and synovial tissues, playing important roles in bone metabolism. Preclinical studies using cannabis-based therapies in animal models have shown that cannabinoids (CBs) can alleviate the development of osteoarthritis (OA), prevent osteoporosis (OP), reduce cancer-induced osteolytic destruction, and improve fracture healing, highlighting the therapeutic potential of CBs for human bone diseases. Conclusions: The present review summarizes various components of the ECS in bone diseases and their potential as a therapeutic target.